A sandwich-like nanofibrous scaffold with macrophage phenotype transformation and myogenic differentiation for skeletal muscle regeneration - Shue Jin; Yongrui Cai; Yaxing Li; Jing Wen; Xiaoxue Fu; Ping Song; Pengyu Lu; Anjing Chen; Zeyu Luo; Weinan Zeng; Jidong Li; Zongke Zhou (Bioactive Materials)
Skeletal muscle injuries caused by trauma, infections, or sports tear are common clinical diseases. Currently, the regeneration and repair of muscle tissue, which is highly heterogeneous, remains a significant challenge. Given the anisotropic structure, high strength and tensile characteristics of skeletal muscle, this study proposes a treatment strategy for muscle injury that combines materials nano-topological cues and biochemical cues. The approach aims to facilitate muscle injury repair through the use of heterogeneous nanofibers on the surface of the sandwich-like electrospun nanofibrous scaffold and macrophage phenotype transformation. Specifically, the outer layer of the sandwich-like scaffold consists of highly aligned fibers, while the middle layer is a core-shell structured random fibers containing hyaluronic acid, and the fiber matrix is composed of optimized proportions of polycaprolactone and gelatin. Mechanical testing shows that the sandwich-like scaffold combines the excellent tensile strength of the outer aligned fibers with the larger elongation at break and suture retention strength of the inner random fibers. Cell and animal experiments confirmed that the aligned fibers in the outer layers guide the cell adhesion, cytoskeleton and nuclear remodeling, and myogenic differentiation of myoblasts, and hyaluronic acid promotes both myogenic differentiation and macrophage phenotype transformation, ultimately accelerating skeletal muscle regeneration. This sandwich-like nanofibrous scaffold provides a novel cell-free, and factor-free approach for the regeneration of skeletal muscle injuries.